Aplicación de un sistema de contabilidad agropecuaria en la hacienda el Jordan, ubicada en la parroquia el Chaupi, canton Mejia, provincia de Pichincha, para el primer trimestre del año 2015 - Chunga Quishpe, Martha Beatriz (2016)
Nowadays, it is possible to observe that many farms in Pichincha Province do not have an adequate economic information, and that is the case of the "El Jordan" Farm that lacks an agricultural accounting system, which is difficulty for the decision making. This research tells in detail on the enterprise, administrative management, accounting, agricultural accounting concepts that allow to implement and execute an adequate accounting system. To the evaluation is carried out the analysis and interpretation of the field investigation results through an interview to the owner, surveys to the employee with the purpose of determining the problem that afflicts the farm. The control of all agricultural and livestock activities is going to be possible with the implementation of an agricultural accounting to obtain reliable information about the environment that involves the process of accounting records, which clearly and accurately reflects economic results to ensure the future of this farm.